The ecology of the plastisphere: Microbial composition, function, assembly, and network in the freshwater and seawater ecosystems - Li, Changchao; Wang, Lifei; Ji, Shuping; Chang, Mengjie; Wang, Longfei; Gan, Yandong; Liu, Jian (Water research (Oxford), 2021)
•Biomarkers of the plastisphere were identified by random-forest machine learning.•Environmental drivers of the plastisphere community variation were explored.•The plastisphere could cause different ecological impacts in different ecosystems.•Niche-based processes govern the assembly of the plastisphere microbial community.•The plastisphere plays a diverse role in microbial networks in different ecosystems. Microplastics provide a unique habitat for microorganisms, forming the plastisphere. Yet the ecology of the plastisphere, including the microbial composition, functions, assembly processes, and interaction networks, needs to be understood. Here, we collected microplastics and their surrounding water samples in freshwater and seawater ecosystems. The bacterial and fungal communities of the plastisphere and the aquatic environment were studied based on 16S and internal transcribed spacer (ITS) high-throughput sequencing. We found that the plastisphere had a distinct microbial community and recruited a noteworthy proportion of unique species compared to the aquatic environment community, potentially altering ecosystem microbial community and causing microbial invasion. Using a random-forest machine-learning model, we identified a group of biomarkers that could best distinguish the plastisphere from the aquatic environment. Significant differences exist in microbial functions between the plastisphere and the aquatic environment, including functions of pathogenicity, compound degradation, as well as functions related to the cycling of carbon, nitrogen, and sulfur. And these functional differences were expressed differently in freshwater and seawater ecosystems. The oxidation-reduction potential, salinity, the concentrations of nitrogen-related ions (NO3−, NO2−, and NH4+), and the concentration of dissolved organic carbon in the surrounding environment drive the variation of the plastisphere. But environmental physicochemical properties explain less of the microbial community variation in the plastisphere than that in the aquatic environment. Niche-based processes govern the assembly of the plastisphere community, while neutral-based processes dominate the community assembly of the aquatic environment. Furthermore, compared to the aquatic environment, the plastisphere has a network of less complexity, more modules, higher modularity, and more competitive links in freshwater ecosystems, but the pattern is reversed in seawater ecosystems. Altogether, the microbial ecology of the new anthropogenic ecosystem—plastisphere—is unique and exerts different effects in freshwater and seawater ecosystems. [Display omitted]